Adherence to therapeutic guidelines among patients treated with statins. Results from STAR study - Degli Esposti, Luca; Sangiorgi, Diego; Lazzeri, Gabriele; Buda, Stefano (Farmeconomia. Health Economics and Therapeutic Pathways, 2012)
INTRODUCTION: the objective of this study was to analyze adherence to therapeutic guidelines among patients treated with lipid lowering drugs (statins). MATERIAL AND METHODS: a retrospective observational study including 5 Local Health Units (LHUs) was conducted using administrative databases. Patients who received at least one prescription for statins between January 1st, 2007 and June 30th, 2008 were selected and followed for 12 months. Patients were classified according to their level of absolute cardiovascular risk (moderate, high, very high according to Nota 13 AIFA). RESULTS: a total of 71,855 patients were included (14,133 newly treated patients with statins, representing 19.4% of total sample), (age 68.8±10.7, male 51%). Level of absolute cardiovascular risk were: moderate risk (45.4%), high risk (33.4%), very high risk (16.3%), familial hypercholesterolemia (4.9%). Statins assumed by patients in analysis were stratified in two groups (first or second choice), accordingly to their efficacy (level of LDL cholesterol reduction) in relation to the patient’s cardiovascular risk (coherently with new Nota 13 AIFA, 2011). Among patients with a very high cardiovascular risk, only 52.8% used statins indicated by Nota13 as a first choice while 2.9% used a second choice statin and 44.3% used an inadequate statin and/or dosage; among familial hypercholesterolemia patients, those percentages were, respectively: 53.8%, 21.1% and 25.1%. When only patients naïve to statins treatment were analyzed, similar percentages were found. Only few patients in very high risk group used adequate dosages: among patients treated with rosuvastatin and atorvastatin, 11.2% used atorvastatin 40 mg, and 0.2% used atorvastatin 80 mg (this population was not analyzed for events because of low numerosity) while 4.1% used rosuvastatin 20 mg and 0.2% used rosuvastatin 40 mg; overall, 84.3% of patients in this group used inadequate dosages. Cardiovascular events at one year of follow up were 1.6% for patients treated with rosuvastatin 20 mg, 1.6% for rosuvastatin 40 mg and 6.1% for atorvastatin 40 mg; death rates (any cause) were 0.9%, 0.0%, 2.6% respectively. The analysis of the sub-population of patients treated with rosuvastatin 20 mg with previous CV event showed a percentage of patients with a CV event during the observational period of 3.4%, a percentage of patients with cerebrovascular event of 0.9% and a mortality percentage of 0.9%. Conclusions: in real practice setting, the percentage of patients prescribed for recommended statins and dosages is low.